Naturalness of the translation of the Quranic imperative verses: A comparative study - Farisi, Mohamad Zaka Al; Tatang, Tatang; Nurmala, Mia; Khalid, Shofa Mushtofa (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The aspects of translation acceptability are not related only to the accuracy and clarity of the translation. They also cover the naturalness of translation. This study aims to reveal the degree of translation naturalness of the Quranic imperative verses. This evaluative study compares the translations of the verses by the Ministry of Religious Affairs of the Republic of Indonesia (MORA) and the one made by Muhammad Thalib (MT). The study used embedded case study research. The findings of the study show that in general, the translations of the verses in the two versions have an acceptable degree of naturalness. However, when both were compared, the translation naturalness of MT’s translation is slightly more acceptable than the one made by the MORA. The translation acceptability of the two translations is inseparable from the translation techniques and procedures used in handling the translation units at the micro-level. The translation techniques such as reduction, transposition, amplification, and the like are deemed as being able to present the translation naturalness of the verses.